HUBUNGAN KETERSEDIAAN PANGAN DAN KONSUMSI ZAT GIZI DENGAN STATUS ANEMIA SISWI SMK NEGERI DI KECAMATAN TABANAN KABUPATEN TABANAN - I Dewa Gede Andre Gunawan; Ida Ayu Eka Padmiari; Anak Agung Gde Raka Kayanaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
ABSTRACT Anemia in adolescents is anemia which is mostly caused by lack of nutrition intake needed for the formation of hemoglobin, namely iron (Fe), vitamin C and copper. The purpose of this study is to determine the relationship of food availability and nutrition consumption with anemia status of State Vocational School students in Tabanan District, Tabanan Regency. This study was an observational study with a cross-sectional approach at SMK Negeri 1 Tabanan in January - March 2020. The population of this study was X grade students of SMK Negeri 1 Tabanan and a sample of 83 people. Anemia status data samples were collected by measuring hemoglobin levels using Hb meters, food availability was obtained using a food record form and nutrition consumption was obtained through interviews using a 1x24 hour recall form. Data were analyzed descriptively and analytically using the Pearson and Spearman Correlation test. A total of 96.4% of the sample were not anemic, 77.1% had food availability in the available category, 54.2% had a low energy consumption level, 32.5% had a low protein consumption level, 88.0% had a very high iron consumption level less, 96.4% had very less consumption of folic acid and 78.3% had very less consumption of vitamin B12. Based on the results of the analysis, it is known that the variable food availability and nutrition consumption that affects the anemia sample status gets p value ɑ (p 0,05)  whick means there is no relationship between food availability and nutrition consumption and there is no relationship between nutrition consumption and anemia sample status.Keywords: food availability, nutrition consumption and anemia status